PENGARUH PENGENDALIAN INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI PADA PT PLN AREA BOJONEGORO) - Nurul Fauziyah (Fakultas Ekonomi, 2018)
The purpose of this study was to determine the effect of internal control and utilization technology information on the quality of financial statements on PLN Area Bojonegoro.Data used this study using primary data obtained from respondents who worked as an accounting section, finance, or administration. The sampling method using a purposive sampling method with the number of respondents is 38 people, 35 usable responses were gathered. Data analysis techniques used include multiple linear regression using SPSS 18.0 for windows. The result showed that (1) internal control are positive and significant effect on the quality of financial statements (2) utilization technology information are positive and significant effect on the quality of financial statements (3) the simultaneous internal control and utilization technology information are positive and significant effect on the quality of financial statements.